Japanese systems : (Sekotac, 1992)
This book introduces about the human basis of Japanese systems, the natural basis of Japanese systems, the social of Japanese systems, the Japanese system of business management, The Japanese systems of information and technology, the Japanese politico-Economic system, the Japanese "Network Society", the working features of Japanese systems, merits and demerits of Japanese systems in the international environment-summary and proposals.